Perception of farmers on seed production constraints of Jatropha curcas L. (Euphorbiaceae) - Datinon, B.; Glitho, I.A.; Tamo, Manuele; Amevoin, K. (Science Alert, 2013)
Many countries have understood that an alternative is needed to the problems of depletion of fossil fuels. Emphasis is therefore put on biofuel-producing crops. One of the most important biofuel-producing plants in tropical is Jatropha curcas L. Several biotic and abiotic constraints limit J. curcas production. The present survey was performed in 13 villages in Benin to assess farmers' perceptions on the biotic constraints. These villages were located in J. curcas production supervised by the non-governmental organization ((Renewable Energy Group, Environment and Solidarity)), One hundred and three producers, representing 25% of the 411 producers of the 3 sites were surveyed. Most producers were illiterate. Only 20 to 40% went to school. About 90% of producers indicated that J. curcas is damaged by pests. During the study, the pictures of the main pests reported in the literature were shown to producers. The producers recognized pests in a proportion of 34, 32 and 43% in Cove, Djidja and Zagnanado, respectively. This shows that most of them could not easily identify pests in pictures. These pests are Meloidogyne incognita (Kofoid and White) Chitwood, Phenacoccus manihoti Matile-Ferrero (Homoptera: Pseudococcidae), Aulocophora africana Lucas (Coleoptera:Chrysomelidea), Stomphastis thraustica Meyrick (Lepidoptera: Graciillariidae), Scutellera nobilis Fabricius (Heteroptera:Scutelleridae) and Pempelia morosalis Saalm Uller (Lepidoptera:Pyralidae). No local name was given to these pests, pointing at the lack of knowledge on their status as pests. Their monitoring is therefore necessary as a first step in order to develop sustainable management methods.